Human exome sequence data in support of somatic mosaicism in carotid atherosclerosis - Alexei A. Sleptcov (Elsevier, 2021)
Understanding the mechanisms underlying the connection between somatic mosaicism and cardiovascular disease is likely essential for the future of personalized medicine. This article is aimed at providing data on somatic mosaicism in human carotid atherosclerosis. An advanced carotid atherosclerotic plaque and white blood cells were collected simultaneously from each patient (eight Slavic males, aged 67 ± 3.8 years [mean ± SD]) to assess the spectrum of germline and somatic genetic variants. Exome sequencing of DNA from the samples was performed with the SureSelect Clinical Research Exome Enrichment Kit (Agilent Technologies) and HiSeq 1500 (Illumina). The dataset contains germline and somatic single-nucleotide variants and small indels identified in the advanced carotid atherosclerotic plaque and white blood cells of each patient. This dataset does not include copy number variants owing to a lack of suitable tools for reliable calculation of copy numbers from exome sequencing data on cancer-unrelated samples. The dataset should help to understand somatic mosaicism in cardiovascular diseases and to identify copy number variants by means of more appropriate newer tools in the future.